Deployment strategy of NFV central office in core network - Lei SHEN; Yongping SHAO; Hai WU (Dianxin kexue)
Central office is the infrastructure for the deployment of communications equipment,and NFV is a telecom cloud with service quality assurance.The needs that collaborative development between core network and computer room was introduced and the status of core network room was analyzed,and the planning of NFV room was proposed from the aspect of transformation strategy of data center and central office and layout of office and quantity planning strategy.